Corruption in health systems: The conversation has started, now time to continue it: Comment on “We need to talk about corruption in health systems” - Lu H.S. (2020)
Holistic and multi-disciplinary responses should be prioritized given the depth and breadth through which corruption in the healthcare sector can cover. Here, taking the Peruvian context as an example, we will reflect on the issue of corruption in health systems, including corruption with roots within and outside the health sector, and ongoing efforts to combat it. Our reflection of why corruption in health systems in settings with individual and systemic corruption should be an issue that is taken more seriously in Peru and beyond aligns with broader global health goals of improving health worldwide. Addressing corruption also serves as a pragmatic approach to health system strengthening and weakens a barrier to achieving universal health coverage and Sustainable Development Goals related to health and justice. Moreover, we will argue that by pushing towards a practice of normalizing the conversation about corruption in health has additional benefits, including expanding the problematization to a wider audience and therefore engaging with communities. For young researchers and global health professionals with interests in improving health systems in the early career stages, corruption in health systems is an issue that could move to the forefront of the list of global health challenges. This is a challenge that is uniquely multi-disciplinary, spanning the health, economy, and legal sectors, with wider societal implications. © 2020 The Author(s).